Mineral Content, Vitamin Profile, and Dietary Fiber Fractions of Aqueous Leaf Extracts from Four Sundanese Traditional Vegetables in Indonesia - Leny Eka Tyas Wahyuni; Hardinsyah Hardinsyah; Budi Setiawan; Nur Rezky Khairun Nisaa; Putri Anggreini (Media of Health Research, 2026)
Lalapan, the traditional Sundanese raw vegetable salad of Indonesia, is a significant component of the daily diet for millions of Indonesians; however, the nutritional composition, particularly the mineral, vitamin, and dietary fiber fractions of its constituent leafy vegetables, remains insufficiently characterized in the scientific literature. Objective This study aimed to determine the mineral content (calcium, potassium, iron, and magnesium), β-carotene, vitamin C, and dietary fiber fractions (soluble, insoluble, and total) in aqueous leaf extracts of four lalapan vegetables: gandaria (Bouea macrophylla), kemangi (Ocimum americanum), pohpohan (Pilea melastomoides), and selada (Lactuca sativa). Methods: Fresh leaves were subjected to aqueous maceration extraction as described. Mineral analysis was performed by atomic absorption spectrophotometry (AOAC 975.03), β-carotene by HPLC (AOAC 45.1.34), vitamin C by titration (AOAC 967.21), and dietary fiber by the enzymatic-gravimetric method. Data are presented as mean ± SD from triplicate analyses. Results: Pohpohan exhibited the highest calcium (1697.05 ± 11.70 mg/100 g) and magnesium (1990.11 ± 6.01 mg/100 g) content, while selada contained the highest potassium (8709.03 ± 34.36 mg/100 g). Kemangi demonstrated the greatest β-carotene concentration (7.69 ± 0.13 mg/100 g), and Gandaria the highest vitamin C (59.66 ± 3.53 mg/100 g). Pohpohan also recorded the highest total dietary fiber (22.11 ± 1.40%) with a predominance of soluble fiber (12.24%). Conclusion: All four lalapan species are nutritionally valuable, with pohpohan and kemangi demonstrating exceptional mineral and vitamin profiles. These findings support promoting lalapan as a functional food component in Indonesian dietary guidelines.